Key Factors in the Expansion of Spanish Communication Groups in Latin America (Communication & Society, 2001)
From 1996, Spanish communication groups have entered into Latin America. The economic and political stability in some American countries, the liberalization of the audiovisual market and the consolidation of the multimedia groups in Spain help to the expansion towards those new markets. The historic and cultural relationship between Spain and America help Spanish companies to lead the European expansion in America. It seems important to study the economic advantages and the information outcomes of these strategies.